Systematic review and meta-analysis of the prevention of internalizing disorders in early childhood - Bolton, Brigid; Rooney, Rosanna Mary; Hughes, Anya; Hopkins, Amber; Mancini, Vincent Oreste (Frontiers in Psychology, 2023)
Internalizing problems comprise a significant amount of the mental health difficulties experienced during childhood. Implementing prevention programs during early childhood may prevent internalizing problems. The present systematic review and meta-analysis aimed to evaluate the effect of both targeted and universal prevention programs in preventing internalizing problems for children aged 3- to 5-years and their parents. PsycINFO, Embase, and MEDLINE were systematically searched, and seventeen randomized control trials, consisting of 3,381 children, met eligibility criteria. There were seven universal prevention programs, and ten targeted prevention programs. Four prevention programs were delivered to children, ten prevention programs were delivered to parents/caregivers, and three prevention programs were delivered to both parents and children. Prevention programs led to significantly fewer internalizing problems at six- and seven-month post-intervention (n = 7, p = 0.02, CI -0.69, 0.06) with a small-to-moderate effect size (g = -0.38), however, not at post-intervention or at 12-month follow up. Overall, findings suggest that there may be value in ongoing development and evaluation of prevention programs for internalizing problems, as they improve social and emotional wellbeing in students and reduce internalizing difficulties within the six- to seven-month timeframe following prevention programs.